Species clarification of the locally famous mushroom Suillus placidus from the south of China with description of S. huapi sp. nov. - Xue, Rou; Chai, Hui; Wang, Yong; Hong, Deng; Su, Ming-Sheng; Liang, Zhi-Qun; Zeng, Nian-Kai (Phytotaxa, 2018)
Collections identified as “S. placidus” from the south of China, a subtropical/tropical region, were investigated using morphology and phylogenetic analyses of DNA sequences from nuc rDNA internal transcribed spacer (ITS). The results indicated that these specimens from subtropical/tropical China are not true S. placidus but represent a new species. Suillus huapi sp. nov. is characterized by a yellowish white to grayish yellow pileus when young, brown to dark brown when old, surface of pores and stipe usually beaded with droplets of milky liquid when young, a stipe without obvious granules, a pileipellis as an ixocutis, and an association with two-needled pines including P. caribaea, P. massoniana and P. yunnanensis.